DEVELOPMENT OF INNOVATIVE MARKETING STRATEGY IN THE DEVELOPMENT OF SERVICES MARKET IN NAMANGAN REGION (Marketing Journal, 2025)
This article examines the role and significance of innovative marketing strategies in the development of the service market in the Namangan region. The research analyzes the dynamics of service sector growth based on digital technologies, modern marketing approaches, and regional characteristics. Growth rates of service volumes in various districts of the region are compared, and the potential for improving service quality and meeting customer needs through the use of innovative strategies is identified. Based on the findings, practical recommendations are provided for effectively applying innovative marketing in the service sector.
Keywords: service market; innovative marketing; digital technologies; Namangan region; service sector; strategy; competitiveness. 117